The firm [videorecording (DVD)] - Cruise, Tom, 1962-; Hackman, Gene; Tripplehorn, Jeanne, 1963-; Pollack, Sydney, 1934-2008 (Widescreen DVD collection., 2007)
A brilliant and ambitious Harvard Law grad joins a small, prosperous law firm in Memphis, and is soon confronted by FBI agents with evidence of corruption and murder within the firm.